PVC Membrane Electrode for the Direct Determination of Chlorpheniramine Maleate in Pharmaceutical Preparations - EL-TOHAMY, MAHA; EL-MAAMLY, MAGDA; SHALABY, ABDALLA (Asian Journal of Chemistry, 2010)
A PVC membrane electrode for chlorpheniramine maleate and phosphomolybdic acid association complex was constructed. The basic electrode's performance characteristics were evaluated. The prepared electrode exhibits a near Nernstian response (57.9 mV per decade) over the concentration range of chlorpheniramine maleate in solutions of pH 4-7. Common organic and inorganic cations showed negligible interference. Direct potentiometric determination of 1 × 10-2-1 × 10-5 M aqueous chlorpheniramine maleate using this membrane electrode system showed an average recovery of 99.9 % with a mean standard deviation of ± 0.811. The electrode gave a good stability reproducibility and fast response. These characteristics of the electrode enable it to be used successfully for the determination of chlorpheniramine maleate in pure form and in pharmaceutical preparations.